Case Report: Pathologic Complete Response to Pembrolizumab in Combination With Neoadjuvant Chemotherapy in a Patient With Stage IIB Squamous Lung Cancer - Zhang, Lin; Mai, Wuqian; Jiang, Wenyang; Geng, Qing (Frontiers in Surgery, 2020)
The emergence of PD-1 antibodies has radically changed the therapeutic profiles of lung cancer, which has the highest incidence and mortality among all cancers in the world. Pembrolizumab, an anti-PD-1 antibody, has been proved to have strong anti-tumor activity in a variety of clinical studies. Here, we described a patient with stage IIB squamous lung cancer who has benefited from a preoperative pembrolizumab plus chemotherapy regimen. The addition of pembrolizumab to neoadjuvant chemotherapy before surgery has lead to pathologic complete response and the avoidance of left pneumonectomy. This case highlights the effect of neoadjuvant pembrolizumab plus chemotherapy on non small cell lung cancer patient and has provided a promising choice in future clinical practice.